Kegagalan Inovasi Daerah di Kota Semarang (Studi Kasus : Inovasi Aplikasi i-Jus Melon Dinas Koperasi dan UMKM Kota Semarang) - Anggita Putri Hanintya; Dzuwanus Ghulam Manar (Journal of Politic and Government Studies, 2020)
Micro and Small Business licensing program based on technology and information on"iJus Melon" application is a program that gives ease to the community by accessing theapplication "iJus Melon" to obtain the legality of micro and small business licenses. Micro andsmall business actors who have registered in the database of Department of Cooperatives andSMES in Semarang will get a business support facility from the government of Semarang, butnot least among the efforts made by the city government Semarang to address problems thathave been constrained by some factors experiencing failure in implementing innovations inpublic service is electronic based. This research uses innovation theory to broaden the scope ofinformation about the implementation of application innovation "iJus Melon" failure becauseit was influenced by several factors when the innovation was realized by the government ofSemarang As an electronic-based public service. After the researchers conducted interviewsand observations showed that the application "iJus Melon" which is not accessible to the onlinecommunity because there is a mismanagement in the application creation system "iJus Melon"and is not known Transparent how to form the cooperation to finally cause problems in theapplication building system "iJus Melon". Secondly, the selection of the term name on theinnovation of public service that does not conform to the substance that will be done so as toinflict mis perception (mis understanding) of the community in understanding the concept ofpublic service based online The. Third, there is no transparency of budget management for theimplementation of application innovation "iJus Melon" conducted by the government. Inaddition, the Department of Cooperatives and SMES have made various efforts to overcomethe problems that arise due to the inhibitory factor that is excessive dependence on the highperformer, obstructed organizational arrangement, not given Incentives, and administrativebarriers despite the implementation have been supported by the encouragement of politicalactors, economic pressures and service improvements, technological availability, andbudgetary availability. Keywords: Failure, Innovation, Application "iJus Melon"